India's Experience with Fiscal Rules : An Evaluation and The Way Forward - Simone, Alejandro; Topalova, Petia (Washington, D.C. : International Monetary Fund, 2009)
This paper examines India's experience with fiscal rules with a view to inform the design of a possible successor fiscal framework to the FRBMA. Among several proposals to strengthen the FRBMA, a framework that focuses medium-term fiscal policy on debt sustainability by the use of a medium term debt target, and annual nominal expenditure growth rules is proposed. This approach tackles the deficit bias at its core and enables countercyclical fiscal policy through automatic stabilizers. Numerical targets should be supported by structural reform measures for both revenues and expenditures, while the coverage of the fiscal rules should be expanded.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet